Pendulum democracy. Towards the structuring of the monopoly of violence in the mexican state - Vázquez Pérez, Eduardo Daniel (2023)
This article aims to demonstrate that, in Mexico, the phenomenon of violence has surpassed the highest authorities and institutions in charge of the system of justice for the benefit of society, a situation that has allowed also, that there is an inability on the part of the latter, in order to guarantee the security and the protection of the human rights of the citizenry to enforce the objectives of the Democratic State and of Law. In Mexico, the increase in violence, sadly, has not diminished but, on the contrary, has increased year after year, so that its impact is severely negative in terms of the development of Mexican society. That said, the phenomenon of systemic violence in the country is not only due to widely organized criminal groups, but is largely generated by the exercise of power to develop normative mechanisms for the protection of human rights, which do not protect them but allow their restriction from the Political Constitution of the United Mexican States (despite its unconventionality), under the discourse of control and manipulation to guarantee the security of people. Consequently, the implementation of the normative devices restricting the exercise of human rights puts the rule of law in crisis and leads it, in leaps and bounds, to a de-civilizing process as will be analyzed and demonstrated in later lines. Finally, it is important to note that the preparation of this article took place within the framework of the celebration of the Doctorate in Intervention in the Organizations of the Metropolitan Autonomous University (UAM), Unidad Azcapotzalco, Mexico City, Mexico.